Irritable bowel syndrome: The incidence of concurrent psychopathology - Margie H Wilson; Anita D Stuart; H Gertie Pretorius (AOSIS, 1999)
The goal of this study was to improve understanding of the association between physiology and psychology in Functional Gastrointestinal disorders by considering the co-morbidity of lrritable Bowel Syndrome and psychopathology in a sector of the South African population. A comparison was made between the incidence of concurrent psychopathology in a sample of 48 white female patients, aged 25 to 55 years and diagnosed with lrritable Bowel Syndrome and the incidence of psychopathology in a control group that consisted of 39 white women, aged 25 to 55 years, who did not meet the criteria for lrritable Bowel Syndrome. The Personality Assessment Inventory was used to determine the incidence of psychopathological personality traits and symptoms in the lrritable Bowel Syndrome group and the control group. This is a selfadministered, objective measuring instrument of adult personality that was developed to provide information about 18 critical clinical variables. The instrument was developed and standardised for use in the clinical assessment of individuals aged 18 years and older. Earlier studies showed a high incidence of associated psychiatric disorder in patients with lrritable Bowel Syndrome. This study confirmed this trend and it seems as if age and level of education has no influence on the incidence of psychopathology in patients with lrritable Bowel Syndrome. Opsomming Dit was die doel van die studie om 'n verbeterde begrip van die assosiasie tussen fisiologie en sielkunde in Funksionele Maagderm Versteurings te bewerkstellig deur die komorbiditeit van Prikkelbare Dermsindroom en psigopatalogie binne 'n sektor van die Suid Afrikaanse populasie te oorweeg. 'n Vergelyking is getref tussen die voorkoms van konkurrente psigopatalogie in 'n steekproef van 48 wit, vroulike pasiente wat wissel in ouderdomme van 25 tot 55 jaar en gediagnoseer is met Prikkelbare Dermsindroom, en die voorkoms van psigopatalogie in 'n kontrolegroep wat bestaan het uit 39 wit vrouens wat nie aan Prikkelbare Dermsindroom ly nie en wie se ouderdomme gewissel het van 25 tot 55 jaar. Die "Personality Assessment Inventory" is gebruik om die voorkoms van psigopatalogiese persoonlikheidtrekke en simptome in die Prikkelbare Dermsindroomgroep en die kontrolegroep te bepaal. Hierdie is 'n self-geadministreerde, objektiewe meetinstrument van volwasse persoonlikheid wat ontwerp is om inligting oor 18 kritiese kliniese veranderlikes te verskaf. Die instrument is ontwikkel en gestandaardiseer vir gebruik in die kliniese taksering van individue vanaf die ouderdom van 18 jaar. Vroesre studies het 'n hoe voorkoms van geassosieerde psigiatriese versteuring in pasiente met Prikkelbare Dermsindroom getoon. Die tendens is bevestig in die studie en dit blyk asof ouderdom of opvoedingsvlak nie 'n invloed het op die voorkoms van psigopatalogie in pasiente met Prikkelbare Dermsindroom nie.